Mixed Bending-Tension (MBT) test for mode I interlaminar and intralaminar fracture - Macedo, F. S.
A new Mixed Bending-Tension (MBT) test is proposed for mode I fracture of laminated composites. The MBT specimen consists of a relatively small pre-cracked laminate adhesively bonded to pin-loaded steel beams. This design reduces significantly the bending stresses that prevent successful application of DCB tests to certain laminates. The MBT was here applied to carbon/epoxy unidirectional [0º]26 and [90º]26 laminates with starter delaminations. Interlaminar initiation GIC values of [0º]26 laminates agreed well with previous DCB test results, while [90º]26 laminates exhibited 50 % higher values. Significant lengths of fairly planar intralaminar crack propagation were seen in the latter laminates. The results showed a fibre bridging related R-curve, which was more pronounced in [0º]26 laminates. The consistency of the present results indicates that the MBT opens new possibilities for the interlaminar and intralaminar mode I fracture.